Surface and electronic characterization of Cu-Zn-Sn shape memory alloys prepared using electrodeless technique - De Los Reyes, Ronald B. (Animo Repository, 2006)
Cu-Zn-Sn shape memory alloy was prepared using electrodeless technique. Compared to other methods, the simple technique of dipping the brass sheet on Sn solution can be easily repeated and tested by bending. The samples were characterized using the scanning electron microscope and Van der Pauw technique. Results indicate that annealing the sample at 700oC and 850oC further reacted the Cu-Zn-Sn mixture as seen in the substantial filling of the surface of the brass sheet. The resistivity of the sample was obtained at 2.31 x 10-4 Ω ’m and 1.24 x 10-3 Ω ’m respectively which was compared to available literature of existing SMA’s.